Foreign Remittances, Foreign Direct Investment, Foreign Imports and Economic Growth in Pakistan: A Time Series Analysis - Muhammad Tahir; Imran Khan; Afzal Moshadi Shah (Arab Economic and Business Journal, 2015)
This empirical research paper focuses on establishing a relationship between external determinants and economic growth of Pakistan economy. Empirical analyses are carried out with time series econometric techniques using data over the period of 1977-2013. The main finding is that external determinants such as foreign remittances, foreign direct investment, and foreign imports matter from a growth perspective. Foreign remittances and foreign direct investment have a significant positive role in the growth process of Pakistan economy. Furthermore, it is found that foreign imports have adversely influenced the economic growth of Pakistan. The study recommends that policy makers shall take appropriate steps to increase the inflow of both foreign remittances and foreign direct investment in order to achieve the long run economic growth.
Keywords: 330; External determinants; Remittances; Foreign direct investment; Imports; Growth; Pakistan